Mewujudkan Pariwisata Tangguh Bencana di Bali: Peran Sertifikasi Kesiapsiagaan Bencana pada Hotel - Ida Ayu Arni Mahasesari (Public Inspiration : Jurnal Administrasi Publik, 2026)
As a global tourist destination, Bali is highly vulnerable to disaster risks that potentially threaten tourist safety and the economic stability of the tourism-based region. To mitigate these impacts, the Provincial Government of Bali established disaster preparedness certification regulations for tourism business operators through Regional Regulation (Perda) No. 5 of 2020 and Governor Regulation (Pergub) No. 52 of 2021. This study aims to analyze the implementation of disaster preparedness certification in Bali's hospitality sector and formulate strategies to support disaster-resilient tourism. This study uses a descriptive qualitative approach. Data collection was conducted through observation, in-depth interviews, and documentation studies at hotels in Bali. The research findings show that the implementation of disaster preparedness certification in Bali's hospitality industry is not yet optimal. The main obstacles are found in the weak aspects of POAC management (planning, organizing, actuating, controlling) and the suboptimal synergy and collaboration among elements in the pentahelix model. The implementation of the hotel disaster preparedness certification policy in Bali still requires structural and operational improvements. Strengthening internal hotel management governance and increasing the commitment of the pentahelix partnership are needed to realize a Bali tourism ecosystem that is truly resilient and safe against disaster threats.